Prevalence of Covid-19 and Associated Co-Morbidities at a Tertiary Hospital in Eastern Nepal - Singh, Randhir Kumar; Singh, Bijoy Lakshmi Dewasy; Mehta, Ram Kumar; Deo, Santosh Kumar (Birat Journal of Health Sciences, 2023)
Introduction: COVID-19 (coronavirus disease) manifests as asymptomatic, mild, or severe pneumonia-like symptoms. COVID-19 patients with diabetes, chronic obstructive pulmonary disease (COPD), cardiovascular disease (CVD), hypertension, malignancies, HIV, and other comorbidities could develop a life-threatening condition.Objectives: To identify the various comorbid illnesses in COVID-19-positive patients along with its baseline characteristics in a tertiary hospital in eastern Nepal.Methodology: A one-month observational study carried out in RT-PCR positive COVID-19 patients in Birat Medical College and Hospital (BMCTH) Molecular Laboratory from June to July 2021. All the data was entered in a pre-structured proforma. The data was then further entered and analyzed by using Microsoft Excel 2014.Result: There were 354 (22.77%) RT-PCR positive COVID-19 cases and 1200 (77.22%) RT-PCR negative COVID-19 cases. More than half of the COVID-19 positive patients were males 211(59.60%). The most common symptoms were fever (92.3%), cough (83.5%) and tiredness (81.23%). Psycho-social stress such as anxiety, depression and insomnia 123 (34.74%) were common comorbidities followed by diabetes 91(25.70%) and hypertension 72(20.33%).Conclusion: COVID-19 patients were mostly between the 20-30 years of age group. Fever, cough, and throat pain were the commonest presenting symptoms.